Making Multicultural Families in Europe Gender and Intergenerational Relations (Palgrave Macmillan Studies in Family and Intimate Life, 2018)
This edited collection explores family relations in two types of 'migrant families' in Europe: mixed families and transnational families. Based on in-depth qualitative fieldwork and large surveys, the contributors analyse gender and intergenerational relations from a variety of standpoints and migratory flows. In their examination of family life in a migratory context, the authors develop theoretical approaches from the social sciences that go beyond migration studies, such as intersectionality, the solidarity paradigm, care circulation, reflexive modernization and gender convergence theory. Making Multicultural Families in Europe will be of interest to students and scholars across a range of disciplines including migration and transnationalism studies, family studies, intergenerational studies, gender studies, cultural studies, development studies, globalization studies, ethnic studies, gerontology studies, social network analysis and social work.‰.